2019
DOI: 10.1507/endocrj.ej18-0217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ipragliflozin on liver function in Japanese type 2 diabetes mellitus patients: a subgroup analysis of the STELLA-LONG TERM study (3-month interim results)

Abstract: This subgroup analysis of STELLA-LONG TERM, an ongoing 3-year post-marketing surveillance study on the long-term efficacy and safety of ipragliflozin, assessed the effect of ipragliflozin on liver function in type 2 diabetes mellitus (T2DM) patients. Patients were divided according to baseline liver function (normal [male: ALT ≤30, female: ALT ≤20], abnormal [male: ALT ≥31, female: ALT ≥21]). We evaluated changes in aspartate aminotransferase (AST), alanine aminotransferase (ALT), gamma-glutamyltransferase (γ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
0
14
0
2
Order By: Relevance
“…A long-term postmarketing surveillance study (STELLA-LONG TERM [Specified drug use resulTs survEy of ipragLifLozin treAtment in type 2 diabetic patients: LONG-TERM use]), was conducted over a period of 3 years in routine clinical practice and registered more than 11,000 patients. Reports based on interim data covering periods of up to 3 months, 12 months, and 2 years after treatment initiation, including subgroup analyses based on age, body mass index (BMI), and hepatic/renal function, have been published previously [21,22,26]. These previous analyses based on interim data have demonstrated that ipragliflozin is well tolerated, including in the elderly and other age subgroups, and maintains glycemic control and body weight reduction for up to 24 months after treatment initiation.…”
Section: Introductionmentioning
confidence: 99%
“…A long-term postmarketing surveillance study (STELLA-LONG TERM [Specified drug use resulTs survEy of ipragLifLozin treAtment in type 2 diabetic patients: LONG-TERM use]), was conducted over a period of 3 years in routine clinical practice and registered more than 11,000 patients. Reports based on interim data covering periods of up to 3 months, 12 months, and 2 years after treatment initiation, including subgroup analyses based on age, body mass index (BMI), and hepatic/renal function, have been published previously [21,22,26]. These previous analyses based on interim data have demonstrated that ipragliflozin is well tolerated, including in the elderly and other age subgroups, and maintains glycemic control and body weight reduction for up to 24 months after treatment initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is proposed that mean FLI was lower and FLI was less accurate www.nature.com/scientificreports www.nature.com/scientificreports/ in NAFLD prediction in Asian studies 31 . However, in recent large-scale Asian population studies in Chinese, Japanese, and Asian-Americans in the U.S., respectively, FLI was recognized and used as a relatively predictable noninvasive diagnostic tool to study of NAFLD also in Asian populations [32][33][34] . Regardless of ethnicity, this is the first study to show the association of periodontitis prevalence with FLI to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The STELLA-LONG TERM study is an ongoing post-marketing surveillance study examining the safety and effectiveness of ipragliflozin in real-world clinical practice in Japan. Several analyses based on interim cutoff data and various subgroup analyses have been conducted so far [12][13][14][15][16] . One of the published subgroup analyses evaluated the safety and effectiveness of ipragliflozin in non-elderly vs elderly patients (<65 vs !65 years) using data from 3, 12 and 24 months.…”
Section: Introductionmentioning
confidence: 99%